Ethical AI in Financial Decision-Making: Balancing Innovation, Regulation, and Social Justice - Muslim, Shohib; Hossam, Ahmed; Abdallah, Mona; Akbarina, Farida (Journal Markcount Finance, 2025)
The integration of Artificial Intelligence (AI) in financial decision-making has revolutionized the sector, offering unprecedented speed and efficiency. However, the increasing reliance on AI systems has raised concerns regarding ethical implications, particularly in terms of fairness, transparency, and accountability. This study explores the intersection of ethical AI, financial decision-making, and social justice, emphasizing the need to balance technological innovation with regulatory oversight and societal impact. The research aims to assess how AI-driven financial decisions align with ethical principles and the role of regulation in ensuring equitable outcomes. A mixed-methods approach was employed, combining a qualitative review of existing literature on AI ethics in finance with quantitative analysis of AI algorithms in decision-making processes within financial institutions. The findings suggest that while AI has the potential to enhance financial decision-making, there is a significant gap in the ethical regulation of AI systems. The study identifies key challenges in ensuring transparency and fairness, particularly in automated lending and investment decisions. It concludes that a comprehensive regulatory framework is essential for balancing innovation with ethical standards, ensuring that AI serves the public good while mitigating the risk of biased decision-making. The findings underscore the importance of social justice considerations in the deployment of AI in financial systems.